A Study on Morphometric Dimensions of Human Fetal Spleen at Different Gestational Ages - D. Srivani; P. Sofia; J. Jayachandra Pillai (Academia Anatomica International, 2020)
Introduction:The spleen is the largest hemolymphatic organ of the human body that plays a significant role in Hematopoiesis and immune phagocytosis. Recent studies have emphasized the importance of spleen as hematopoietic organ in fetal period, role in synthesis of immunoglobulins & defense of human body against infections. A thorough knowledge of splenic morphometry and dimensions is vital in comprehending the development of spleen in fetal period.Aim:The aim of the study is to study detailed morphometric analysis human fetal splenic specimens of various gestational ages and compare the findings with earlier studiesSubjects and Methods:The present study included 40 fetal cadaveric spleen and morphometric features i.e.,length, breadth, width and weight of spleen were measured.Results:The average weight of the fetal spleen was 1.98 gm and varied from 0.1 to 5.1 gm. The average length, breadth and width of spleen in prenatal group were 2.21 cm, 1.39 cm and 0.645 cm respectively. In the present study the average weight of the fetal spleen was 1.98 gm and varied from 0.1 to 5.1 gm. There was statistically significant increase in splenic weight till 33 weeks.Conclusion:Knowledge of spleen size at different gestational ages will help in early detection and diagnosis of splenic anomalies, identifying congenital malformations, early diagnosis and prompt treatment of intrauterine infections.